Hubungan Fungsi Kognitif Dan Dukungan Keluarga Dengan Kemandirian Lansia Dalam Activity Of Daily Living (ADL) Di Desa Hauagong - Napitupulu, Arnol; Wahyu, Afnijar (Indonesian Trust Nursing Journal, 2025)
Elderly people are an advanced stage of a life process which is characterized by a person'sphysical decline, which can result in a decline in social roles. This also causes disruption inmeeting their daily needs, which can increase dependency and require help from otherpeople. The objective of this study is to determine the relationship between cognitivefunction and family support with the independence of elderly people in activities of dailyliving (adl) in Hauagong Village. The research Method is quantitative research with a cross-sectional study design. The sampling technique in this research was Total Sampling,however when the research was carried out there were 50 respondents present, so thesample in this research was 50 respondents. Data analysis used the Pearson correlationtest. The results of this study using the Pearson correlation test show that there is arelationship between cognitive function and the independence of the elderly in activities ofdaily living with a p-value = 0.000 α < 0.05, and there is a significant relationship betweenfamily support and the independence of the elderly in activities of daily living with p-value =0.017 α < 0.05. It is concluded that there is a relationship between cognitive function andfamily support and elderly independence in daily activities. It is recommended to carry outfurther research with a larger sample and add variables of anxiety level, sleep quality andrheumatoid arthritis pain, because this also affects the level of independence in the elderly.